Cloning and Functional Characterization of a Double-Stranded RNA-Degrading Nuclease in the Tawny Crazy Ant (Nylanderia fulva) - Lei, Jiaxin; Tan, Yongan; List, Fabian; Puckett, Robert; Tarone, Aaron M.; Vargo, Edward L.; Zhu-Salzman, Keyan (Frontiers in Physiology, 2022)
RNA interference is a powerful tool that post-transcriptionally silences target genes. However, silencing efficacy varies greatly among different insect species. Recently, we attempted to knock down some housekeeping genes in the tawny crazy ant (Nylanderia fulva), a relatively new invasive species in the southern United States, but only achieved relatively low silencing efficiency when dsRNA was orally administered. Here, we detected divalent cation-dependent, dsRNA-degrading activity in the midgut fluid of worker ants in ex vivo assays. To determine whether dsRNA degradation could contribute to low effectiveness of oral RNAi in N. fulva, we cloned its sole dsRNase gene (NfdsRNase). The deduced amino acid sequence contained a signal peptide and an endonuclease domain. Sequence alignment indicated a high degree of similarity with well-characterized dsRNases, particularly the six key residues at active sites. We also identified dsRNase homologs from five other ant species and found a tight phylogenetic relationship among ant dsRNases. NfdsRNase is expressed predominantly in the abdomen of worker ants. Oral delivery of dsRNA of NfdsRNase significantly reduced the expression of NfdsRNase transcripts, and substantially suppressed dsRNA-degrading activity of worker ants’ midgut fluids as well. Our data suggest that dsRNA stability in the alimentary tract is an important factor for gene silencing efficiency in N. fulva, and that blocking NfdsRNase in gut lumen could potentially improve RNAi, a novel pest management tactic in control of N. fulva and other ant species.